Cooperative Learning (CL) in Promoting Oral Group Lessons - Wondwosen Tesfamichael Ali (Budapest International Research and Critics University, 2019)
The purpose of this study was to assess whether or not the oral group lessons in the student English textbook of grade seven promoted CL. The study involved in the textbook, two English language teachers and one hundred twenty students who have been teaching and learning the English language, respectively at Muke Turi Primary and Junior Secondary School in Northern Shoa, Ethiopia. The data for the study were gathered through text analysis. In order to see the actual happening and to triangulate the findings of the text analysis, interviews were conducted and classrooms were observed. The results of the study showed that the oral group lessons in the textbook of grade seven fulfilled almost all the criteria of CL; the teachers and the students who were interviewed understood the benefits of sharing ideas through group work which in turn promotes CL though the number of the students in the class was large, and the students had poor background knowledge of English. The classroom observations proved that the number of students in the class was large; the desks were fixed; the students frequently used their mother tongue rather than English during group discussions; the teachers did not set a time limit for the discussions, and there were few practices of evaluating the oral group lessons after group discussions. The findings of this study indicate that the oral group lessons in the textbook helped to promote CL though there were problems to practice them in the classrooms.